Frequency of CMV- Infection among Hemodialysis Patients in Tikrit City - Hashim Saadoon, Israa (Iraqi Journal of Science, 2023)
It has been well documented that hemodialysis patients have impaired immune response, which may result in higher prevalence rates of viral infections, including CMV. Infections in these patients may be due to primary infection or, more commonly, by reactivation of latent virus or re-infection with exogenous virus, which may be introduced by blood transfusion. The aim of this study was to evaluate the frequency of CMV-IgG and IgM antibodies among hemodialysis patients. The current research included 116 hemodialysis patients (69 male and 47 female) who attended to Tikrit Teaching Hospital for the period from beginning of October/2013 to the end of April/2014. CMV-IgG was found in 102 out of 116 (87.9%), while CMV- IgM was detected in 10 out of 116 (8.6%) of hemodialysis patients. CMV-IgG was found in a higher rate in females than that in males (91.5% and 85.5% respectively), while CMV-IgM was detected in a higher rate in males than that in females (10.1% and 6.4% respectively). However, there was non-significant difference (p> 0.05) between sex and seropositivity. Also, non- significant relation was found between age and seropositivity for both CMV-IgG and CMV-IgM antibodies (p> 0.05). Since patients receiving hemodialysis treatment are immunocompromised and can be at risk of primary infection or reactivation of latent infection of CMV, its necessary to identify these patients with anti-CMV IgG and IgM specific serological tests for appropriate management.